Genome-wide association study of subcortical brain volume in PTSD cases and trauma-exposed controls. Issue 11 (November 2017) - Morey, Rajendra; Davis, Sarah; Garrett, Melanie; Haswell, Courtney; Marx, Christine; Beckham, Jean; McCarthy, Gregory; Hauser, Michael; Ashley-Koch, Allison
Abstract Depending on the traumatic event, a significant fraction of trauma survivors subsequently develop PTSD. The additional variability in PTSD risk is expected to arise from genetic susceptibility. Unfortunately, several genome-wide association studies (GWAS) have failed to identify a consistent genetic marker for PTSD. The heritability of intermediate phenotypes such as regional brain volumes is often 80% or higher. We conducted a GWAS of subcortical brain volumes in a sample of recent military veteran trauma survivors (n  = 157), grouped into PTSD (n  = 66) and non-PTSD controls (n  = 91). Covariates included PTSD diagnosis, sex, intracranial volume, ancestry, childhood trauma, SNP×PTSD diagnosis, and SNP×childhood trauma. We identified several genetic markers in high linkage disequilibrium (LD) with rs9373240 (p  = 2.0 × 10−7, FDRq  = 0.0375) that were associated with caudate volume. We also observed a significant interaction between rs9373240 and childhood trauma (p -values = 0.0007–0.002), whereby increased trauma exposure produced a stronger association between SNPs and increased caudate volume. We identified several SNPs in high LD with rs34043524, which is downstream of theTRAM1L1 gene that were associated with right lateral ventricular volume (p  = 1.73 × 10−7 ; FDRq  = 0.032) and were also associated with lifetime alcohol abuse or dependence (p  = 2.49 × 10−7 ; FDRq  = 0.0375). Finally, we identified several SNPs in high LD with rs13140180 (p  = 2.58 × 10−7 ; FDRq  = .0016), an intergenic region on chromosome 4, and several SNPs in theTMPRSS15 associated with right nucleus accumbens volume (p  = 2.58 × 10−7 ; FDRq  = 0.017). BothTRAM1L1 andTMPRSS15 have been previously implicated in neuronal function. Key results survived genome-wide multiple-testing correction in our sample. Leveraging neuroimaging phenotypes may offer a shortcut, relative to clinical phenotypes, in mapping the genetic architecture and neurobiological pathways of PTSD.